PERAN KELOMPOK KERJA GURU (KKG) PENDIDIKAN AGAMA ISLAM DALAM MENINGKATAN KOMPETENSI PAEDAGOGIK GURU DI SEKOLAH DASAR NEGERI GUGUS KECAMATAN PAYARAMAN KABUPATEN OGAN ILIR - Abdul Gani (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2014)
Abstract. This thesis background by the limitations of the board of KKG, these limitations can be seen from the human resources is minimal, because most teachers of Islamic education in elementary schools would not be a caretaker select KKG, further involvement KKG administrators and teachers of Islamic education are less coordinated one each other so that the work program does not involve teachers of Islamic education. In addition, the perception of Islamic education teachers to KKG only a gathering of teachers. Thus the focus of the problem in this study were (1) How the Implementation of Teachers Working Group (KKG) PAI in State Primary School Cluster District of Payaraman ?; (2) How Kedesiplinan Islamic Education Teachers in following activities Teachers Working Group (KKG PAI) District of Payaraman ?; (3) How pedagogical competence of teachers in the State Primary School PAI Force District of Payaraman?The study was descriptive qualitative research respondents of 16 people, consisting of five principals and 11 teachers PAI. Data collection tool was an interview, observation and documentation. While the descriptive data analysis techniques.The study aims to determine the Implementation of Teachers Working Group (KKG) PAI in State Primary School Cluster District of Payaraman, knows discipline teacher of Islamic education in the following activities PAI KKG District of Payaraman, and to determine the pedagogical competence of teachers in the State Primary School PAI Force District of Payaraman .The results of the research are: (1) Conducting a Teacher Working Group (KKG) PAI District of Payaraman already performing well. It can be seen from the program of activities has been arranged systematically and in accordance with the problem, (2) Discipline Islamic Education teachers in follow KKG is good, it can be seen from the presence of the participants (teachers) in the District of KKG PAI Payaraman, Further seen from the liveliness of teachers (participants KKG) to ask questions, respond to other teachers questions, share information with the interaction of many directions, ie participants and participant with tutors and fellow tutors, 3) pedagogical competence of teachers of Islamic Education elementary School has a good group namely learning program prepared properly, then the learning and assessment program based on the preparations that had been developed previously. Keywords: Role of Teachers Working Group (KKG) Islamic Education and Competence paedagogik Teachers